Boosting oxygen evolution reaction of transition metal layered double hydroxide by metalloid incorporation. (September 2020) - Han, HyukSu; Kim, Kang Min; Ryu, Jeong Ho; Lee, Ho Jun; Woo, Jungwook; Ali, Ghulam; Chung, Kyung Yoon; Kim, Taekyung; Kang, Sukhyun; Choi, Seunggun; Kwon, Jiseok; Chung, Yong-Chae; et al.
Abstract: Transition metal layered double hydroxides (LDHs) have received much attention as high-performance oxygen evolution reaction (OER) catalysts due to their large number of active sites with favorable adsorption/desorption energies for intermittent reactants. However, the relatively sluggish charge transfer kinetics of transition metal LDHs due to their intrinsically low conductivity often hinders their use in practical applications as high-performance water oxidation catalysts. Here, we disclose a novel strategy of metalloid incorporation into transition metal LDHs, allowing us to simultaneously optimize surface electronic configuration and charge transfer between adsorbed reactants and catalyst surface. Importantly, incorporated metalloid can enhance the density of states (DOS) near the Fermi level and alter the nature of the chemical bonds in the catalytically active atoms, resulting in fast reaction kinetics. Thus, metalloid incorporation into transition metal LDHs can substantially improve the overall reaction kinetics and thermodynamics for water oxidation due to a large number of active sites and high conductivity, boosting OER performance of transition metal LDHs. The metalloid-incorporated transition metal LDHs far outperform their counterpart transition metal LDHs and even the noble metal catalyst RuO2 . Graphical abstract: Metalloid incorporation into transition metal LDHs can be a promising strategy for designing highly efficient and robust electrocatalysts for alkaline OER. Image 1 Highlights: Atomic scale engineering using metalloid elements for transition metal layered double hydroxides (LDHs) is firstly developed. Strategic tellerium (Te) incorporation at the atomic level on edge cobalt (Co) sites is found to be crucial for the improvement of electrical conductivity. Tailored d-band electronic structure occured via p-d hybridization when Te incorporates into NiCo-LDHs leading to enhanced water oxidation properties. Te-NiCo LDHs shows very low overpotential of 190 mV at a current density of 10 mA cm -2, respectively, with the lowest Tafel slope of 23.38 mVdec -1 for water oxidation. Density functional theory (DFT) calculations revealed individual roles of elements in Te-NiCo LDHs for water oxidation.